Handbook for Legislators on HIV/AIDS, Law and Human Rights - Peter Piot, Anders Johnsson (Geneva, Switzerland, 1999)
The Handbook provides examples of best legislative and regulatory practices gathered from around the world. Best practices are given for each of the twelve guidelines contained in the International Guidelines on HIV/AIDS and Human Rights published in 1998 by the Office of the United Nations High Commissioner for Human Rights and the Joint United Nations Programme on HIV/AIDS (UNAIDS).